Uwarunkowania efektywności kształcenia nauczycieli klas I-III w zakresie twórczości pedagogicznej - Magda-Adamowicz, Marzenna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Creativity of early school teachers is possible because everyone carries out ordinary intellectualopearions. Creativity expands the frames of our lives, making a human being unique andcheerful and it enables to reach valuable values of development, which conteracts negativesymptoms of contemporary civilisation.
Keywords: nauczyciele nauczania początkowego; myślenie twórcze; szkolenia; pedagogika; nauczanie; efektywność; szkolnictwo wyższe; Polska; od 1989 r.